Contribution of increased apoptosis in monocytes and lymphocytes in the etiopathogenesis of systemic lupus erythematosus (SLE) - Che Maraina, Che Hussin (Pusat Pengajian Sains Perubatan, 2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease involving multiple organ systems and production of a wide array of autoantibodies. The aetiopathogenesis remains unknown but the complex combination of environmental trigger (infection and UV exposure) and genetic factors seems to be involved. Data from human SLE reported an increased apoptosis and defective clearance of apoptotic cells and suggested to have a pathogenic role in development of SLE. Increased apoptosis of circulating and in vitro in variety of cells such as monocytes, lymphocytes, neutrophils, as well as cell line was demonstrated in SLE. Previous reports suggested that the serum factors could induce apoptosis in SLE. Therefore this study is conducted I) to compare the in vitro mean proportion of apoptosis in monocytes and lymphocytes in active with inactive SLE patients, 2) to compare the in vitro mean proportion of apoptosis in monocytes and lymphocytes in SLE patients with normal controls and 3) to determine the correlation of apoptosis in SLE patients with serum factors. A total of248 subjects were enrolled in this study, 124 subjects for each group of healthy controls and SLE patients ( 62 active SLE and 62 inactive SLE). All the patients fulfilled four or more of the American Rheumarism Association Classification Criteria for SLE (1987).Subjects recruited fulfilled the inclusion and exclusion criteria. Blood was withdrawn into EDTA (I ml) for full blood count and plain tubes (9 ml) for apoptosis and serum factors analysis. Statistical analyses were performed using the SPSS version 18.0. Results revealed that both apoptotic lymphocytes and monocytes was significantly higher in SLE patients compared to normal controls (p=O.OO I and p=0.030) respectively. Both apoptotic lymphocytes and monocytes was also significantly higher in active SLE compared to inactive SLE patients (p<0.042 and p<0.028) respectively. According to Pearson's correlation test, apoptotic lymphocyte was significantly correlated with C3(0.007), C4(0.034), TNFa(0.012), anti-dsDNa antibodies(0.029) and anti-Clq autoantibodies(0.036) but not with C5a, sFas ligand and ACL antibodies. Apoptotic monocytes was also significantly correlated with C3(0.00 1), C4(0.008) and TNFa(0.003). The simple linear regression showed no significant relationship between both apoptotic lymphocytes and monocytes with CRP (P>0.05). The results of this study suggest that circulating factors in the serum of the SLE patients are responsible for the apoptosis and may play a pathogenic role in SLE.